Middle-income trap and factors affecting the risk of growth slowdown in upper-middle-income countries - Ursavaş, Uğur; Sarıbaş, Hakan (Economics and Business Letters, 2020)
In this paper, we investigate the macroeconomic, demographic and institutional factors affecting the probability of growth slowdown in upper-middle-income countries within the framework of the growth slowdown methodology developed by Eichengreen et al. (2011). To do so, we use probit regression, and the dataset covers the period 1980-2015. The results show that growth slowdown occurs when per capita income reaches 22 percent of that in the United States. Besides, an increase in the relative income, gross capital formation, trade openness, years of total schooling, old dependency ratio and law and order index increases the risk of growth slowdown, whereas an increase in public debt, inflation variability and years of secondary and higher schooling decreases the risk of growth slowdown.